PENGARUH PROPORSI KOMISARIS INDEPENDEN TERHADAP KINERJA KEUANGAN PERUSAHAAN (PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BEI) - Firdha Desi Triani; Makhdalena '; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine whether the proportion of independent commissioners affect the financial performance of the company. For financial performance measured by Retrun on Asset. This study was conducted using secondary data in the form of annual reports of manufacturing companies published on IDX (Indonesian Stock Exchange) website during 2013-2015. The sample in this research are 14 food and beverage companies listed in BEI year 2013-2015. Data analysis method used is simple linear regression analysis. The result of the research shows that the Independent Board of Commissioner's Proportion has an effect on to Company's Financial PerformanceKeywords : Independent Board of Commissioner's Proportion, Company's Financial Performance